Construction of a large road infrastructure in a metropolitan area; what can the analysis of community complaints to noise tell us? - Alexis Pinsonnault-Skvarenina; Véronique Guay; Renaud Leblanc-Guindon; Mathieu Carrier; Annelies Bockstael; Jean-Pierre Gagné; Tony Leroux (Environmental Impact Assessment Review, 2024)

Pelagic production and the recruitment of juvenile polar cod Boreogadus saida in Canadian Arctic seas - Mathieu LeBlanc; Maxime Geoffroy; Caroline Bouchard; Stéphane Gauthier; Andrew Majewski; James D. Reist; Louis Fortier (Polar Biology, 2020)
Previous work found that an earlier ice breakup favors the recruitment of juvenile polar cod ( Boreogadus saida ) by enabling early hatchers to survive and reach a large size by late summer thanks to a long growth season. We tested the hypothesis that, in addition to a long growth season, an earlier ice breakup provides superior feeding conditions for young polar cod by enhancing microalgal and zooplankton production over the summer months. Ice cover and surface chlorophyll a were derived from satellite observations, and zooplankton and juvenile cod biomass were estimated by hydroacoustics in ten regions of the Canadian Arctic over a period of 11 years. Earlier breakups resulted in earlier phytoplankton blooms. Zooplankton backscatter in August increased with earlier breakup and bloom, and plateaued at chlorophyll a > 1 mg m −3 . Juvenile cod biomass in August increased with an earlier breakup, and plateaued at a zooplankton backscatter > 5 m 2 nmi −2 , supporting the hypothesis that higher food availability promotes the growth and survival of age-0 fish in years of early ice melt. However, there was little evidence that late summer biomass of either zooplankton or age-0 polar cod benefitted from ice breakup occurring prior to June. On average, zooplankton standing stock was similar in the Southern Beaufort Sea and the North Water-Lancaster Sound polynya complex, but juvenile cod biomass was higher in the Beaufort Sea. Intense avian predation could explain the lower biomass of juvenile cod in the polynya complex, confirming its reputation as a biological hotspot for energy transfer to higher trophic levels.

Vertical segregation of age-0 and age-1+ polar cod (Boreogadus saida) over the annual cycle in the Canadian Beaufort Sea - Maxime Geoffroy; Andrew Majewski; Mathieu LeBlanc; Stéphane Gauthier; Wojciech Walkusz; James D. Reist; Louis Fortier (Polar Biology, 2016)